Southpaw [videorecording (DVD)] - Gyllenhaal, Jake, 1980-; McAdams, Rachel, 1978-; Whitaker, Forest (Anchor Bay Entertainment, 2015)
Billy "The Great" Hope, reigning Light Heavyweight Boxing Champion of the World, seemingly has it all: an impressive career, a beautiful and loving wife, an adorable daughter, and a lavish lifestyle. When tragedy strikes and his lifelong manager and friend leaves him behind, Hope hits rock bottom and turns to an unlikely savior at a run-down local gym: Tick Willis, a retired fighter and trainer to the city's toughest amateur boxers.